Pelatihan Dasar Shutterstock Sebagai Media Penyedia Konten Visual Bagi Siswa/i SMK 1 Pantai Labu - Hasibuan, Ade Zulkarnain; Munjiat Setiani Asih; Siti Sundari; Edrian Hadinata; Khairunnisa (Jurnal Pengabdian Masyarakat, 2023)
Community service activities are carried out at SMK 1 Pantai Labu, the main target of this activity is students majoring in software engineering. The activities carried out discussed the Shutterstock platform for selling digital works of students at SMK 1 Pantai Labu. The thing that underlies this activity is the students' lack of knowledge regarding digital works that can be sold all over the world just by uploading them to the Shutterstock platform without having to pay for the upload process. Many of the digital works they have so far have only been stored on hard disks or on the SSD they own or just post it on social media without any financial benefit.